(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to identify the degree of practicing administrative empowerment among school principals from the point of view of teachers in government secondary schools in Zarqa Governorate, and to determine whether there were statistically significant differences between the average responses of the study sample members according to the variables (gender, academic qualification, and years of experience). To achieve the study objectives, the descriptive correlational approach was adopted, and the sample was selected randomly, amounting to (309) individuals at a rate of (19.8%) of the study community. The questionnaire, which consisted of one part, was used to measure the degree of practicing administrative empowerment among government secondary school principals, and consisted of (18) paragraphs. The results showed that the degree of practicing administrative empowerment among government secondary school principals in Zarqa Governorate as a whole and for all fields was average, and there were no statistically significant differences between the responses of the sample members to the degree of practicing administrative empowerment among government secondary school principals according to the variables (gender, academic qualification, and years of experience).